THE INFLUENCE OF SALARY COMPENSATION ON EMPLOYEE PERFORMANCE IN SHENGSHITONGDA: A QUALITATIVE INVESTIGATION - Wang Xiao Dong; Ooi Kok Loang (Journal of Islamic, Social, Economics and Development, 2023)
Salary compensation is a critical factor in employee motivation and performance, as it plays a significant role in attracting and retaining talented employees. This study aims to investigate the influence of salary compensation on employee performance in Shengshitongda, a leading logistics company in China. The study adopts a qualitative research approach, using in-depth interviews with employees to collect data. The results of the study suggest that salary compensation is a crucial factor in employee motivation and performance, and a fair and transparent compensation system positively influences employee satisfaction and loyalty. The study also found that employees who perceived their salaries to be inadequate or unfair were more likely to have lower job satisfaction and reduced productivity. Furthermore, the study revealed that employees value non-financial benefits, such as career development opportunities and work-life balance, in addition to salary compensation. The findings of this study have practical implications for human resource managers and business leaders in Shengshitongda and other logistics companies, highlighting the importance of designing a comprehensive and fair compensation system to attract and retain talent, enhance employee performance, and achieve organizational goals.